THE INFLUENCE OF INFLUENCER MARKETING AND FASHION TRENDS ON PURCHASE DECISIONS THROUGH CONSUMER TRUST IN THE TIKTOK SHOP APPLICATION AMONG GENERATION Z IN PALU CITY - Cinta Nur Ahda Febriyanti; Wahyuningsih; Muzakir; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Influencer Marketing and Fashion Trends on Purchasing Decisions through Consumer Trust on the TikTok Shop application among Generation Z in Palu City. The study uses a quantitative approach with an associative research type. The study population is Generation Z in Palu City who have made purchases through TikTok Shop. The research sample consisted of 112 respondents selected using a purposive sampling technique. Data collection was carried out by distributing questionnaires with a five-point Likert scale. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS 4.0 software. The results of the study indicate that Influencer Marketing has a positive and significant effect on Consumer Trust and Purchasing Decisions. Fashion Trends also have a positive and significant effect on Consumer Trust and Purchasing Decisions. In addition, Consumer Trust has a positive and significant effect on Purchasing Decisions. The results of the mediation test indicate that Consumer Trust is able to mediate the influence of Influencer Marketing and Fashion Trends on Purchasing Decisions. The findings of this study indicate that the better the influencer marketing strategy and the higher the product's suitability to fashion trends, the higher consumer trust will be, which ultimately increases purchasing decisions on the TikTok Shop application among Generation Z in Palu City.